A Multimodal Discourse Analysis Of Meaning Construction Through Verbal And Non-Verbal Modes In Selected Ted Public Speeches On Climate Change - Zhang, Wenna (2024)
This study explores how various symbolic resources embodied in TED talks contribute to forming meaningful units. The purposive sampling was employed to select twenty TED talks on climate change from 2019 to 2022, examining verbal and nonverbal elements based on multimodal discourse analysis. In addition, the qualitative method and textual analysis were utilised in this study to investigate the dominant themes, meaning construction through verbal and non-verbal modes and the interplay between these two modes in selected TED talks on climate change. To achieve these research objectives, the study combines the following theoretical framework: 1) Halliday’s Systemic Functional Linguistics (2004) is utilised to discuss the verbal mode, focusing on transitivity, mode, modality, personal pronoun, and thematic structure; 2) Kress and Van Leeuwen’s Visual Grammar (1996) is applied to explore nonverbal modes such as gesture, eye contact, slide, and videos; 3) Martinec and Salway’s Text-Image Relation Theory is used to analyse the interaction between the verbal mode and slides. The study’s findings examine the characteristics of verbal and nonverbal modes and elucidate how they contribute to reinforcing speakers’ messages in TED talks. Above all, TED talks on climate change prioritize solutions over highlighting the issues caused by climate change.